Pendidikan Kematian: Memaknai Maut Menjadi Sebuah Kerinduan - Mumtazul Fikri (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2014)
The death would not be able to be separated from human life, because everything that lives must feel death. In waiting for the death coming human always in the anxiety and the fear, except for them who worshipped Allah SWT. Actually, the death is not the end of journey; otherwise, it’s the beginning of human life in the eternal and immortal place at the longest. The death education is the awareness effort of people opinion about the true concept of death itself in order to achieve the highest destination of human life. The philosophy of death education have to be understood by entire Muslim in order the death would not be the anxiety and the fear; however, it will become a yearning. Kata Kunci: Pendidikan Kematian, Istisyhadiyah, Jihad